SOLATION AND CHARACTERIZATION OF TWO XANTHONES GENTIANELLA THYRSOIDEA HOOKER FABRIS - Tomás-chota, G. (1999)
In researching the Gentianella thyrsoidea (root, stem, flower) were isolated 3-0I-1,5,8-0H xanthone (Bellídifolina) 1 and 1,8-0H-3,5-0I xanthone (Swerchirina 2) . The structures were elucidated by spectroscopic methods (UV, 1H-NMR, NMR13C, DEPT, MS).